Produção do conhecimento na educação física: análise epistemológica dos anais do grupo de trabalho temático “inclusão e diferença” do Colégio Brasileiro de Ciências do Esporte (CBCE) DE 2003 A 2013 - Fernandes, Ilnah de Oliveira (2016)
The object of study and analysis of this research are the articles published in the Thematic Working Group Inclusion and Difference proceedings Inclusion and Difference of the Brazilian Congress of Sports Sciences, between 2003 and 2013. The general objective is to identify the epistemological bases present in the production of knowledge in Physical Education, from the annals of the mentioned Thematic Working Group, and how these bases respond to the issue of inclusion of students with disabilities. For this purpose, we present how to constitute the relationship between the characterization of the research, the main issues addressed and the inclusion perspectives found in each approach. Using an analytical tool in consonance with the paradigmatic matrix, that points out the technical, methodological, theoretical and epistemological levels. This methodological procedure made it possible to realize, in the 31 articles analyzed, that 90% used the Phenomenological-Hermeneutic approach and 10% used the Critical-Dialectic approach, and has not identified any article used the Empirical-Analytical approach. We found that each level of the instrument used for analysis of the articles made evident the predominance of the approach taken, in other words, in the articles in which the Phenomenological-Hermeneutic approach was predominant, it was observed that the discussion is focused on understanding the phenomena and where these have as a base. In the articles using the Critical-Dialectic approach we note that the discussion was taking as a basis the issues of social context and its alternative processing. Given the limitations found in this research, both personal and time to deepen some debate, it is necessary that further research be done in order to expand and advance the contributions in the knowledge production of physical education, and exclusion / inclusion, pointing out the various conflicts that implies in this context.